Pengelolaan Buah Pinus dalam Peningkatan Keterampilan Karang Taruna Kelurahan Kaisabu Baru - Dwi Agustyawati; Rusdin Rusdin (BADAN PENERBIT STIEPARI PRESS, 2021)
This community service activity focuses on 1) Providing training and new knowledge to the members of the Kaisabu Baru youth group 2) Improving the skills of Karang Taruna to earn additional income through the utilization of pine nuts into a product with selling value, which can later be marketed to tourists who visited the tourist attraction of the Samparona Pine Forest. The method used in this activity was training which was directly taught to cadet members, totaling 20 people who were managers of the Samparona Pine Forest tourism park. The benefits that can be directly felt by members of youth organizations are increasing skills in utilizing pinecones and processing them into goods that have a sale value so that they can provide additional income. This service was carried out at the Samparona Pine Forest Tourism Object in Kaisabu Baru for one day by providing direct training and outreach. The output to be achieved in this community service is a community service journal that is published and is expected to be able to apply knowledge in managing pinecone waste in entrepreneurship.